2017
DOI: 10.2174/1567205013666160930110551
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Necrosis Factor Alpha for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) affects an estimated 44 million individuals worldwide, yet no therapeutic intervention is available to stop the progression of the dementia. Neuropathological hallmarks of AD are extracellular deposits of amyloid beta (Aβ) peptides into plaques, intraneuronal accumulation of hyperphosphorylated tau protein forming tangles, and chronic inflammation. A pivotal molecule in inflammation is the pro-inflammatory cytokine TNF-α. Several lines of evidence using genetic and pharmacological mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
212
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(239 citation statements)
references
References 185 publications
9
212
2
Order By: Relevance
“…Decreased levels of IL-8 in patients with AD were linked to descending reparative mechanism in the central nervous system (CNS) 7. The proinflammatory cytokine TNF-α and its receptors sTNFR1 and sTNFR2, which regulate numerous physiological processes in CNS, have been detected to exacerbate the main pathological changes of AD (both Aβ and tau pathologies) in vivo 25. Our meta-analyses proved notable variances in the peripheral concentrations of sTNFR1 and sTNFR2 between group comparisons, implying that these markers may be useful in helping to monitor disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of IL-8 in patients with AD were linked to descending reparative mechanism in the central nervous system (CNS) 7. The proinflammatory cytokine TNF-α and its receptors sTNFR1 and sTNFR2, which regulate numerous physiological processes in CNS, have been detected to exacerbate the main pathological changes of AD (both Aβ and tau pathologies) in vivo 25. Our meta-analyses proved notable variances in the peripheral concentrations of sTNFR1 and sTNFR2 between group comparisons, implying that these markers may be useful in helping to monitor disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the neuropathological parameters of AD such as aggregation of phosphorylated tau protein, Aβ deposition, and activated microglial and astrocyte cell were all observed to be reduced by the inhibition of the TNF-α pathway. It's worth to mention that prevention of this signaling cascade inhibits the strong stimulation of microglial cells, keeping them in a state of moderate stimulation where they play a neuroprotective role by elevating of βAPP clearance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the current analysis also showed that in older lungs, AEP and Macrophages both have TNFα levels significantly increased ( Figure 1G, Supplementary Figure S1F). Along with the gene expression signature described above, it is plausible aged baseline inflammation very likely be a result of the increased beta-amyloid load (Decourt et al, 2017). ADAM17 member of "A Disintegrin And Metalloprotease" (ADAM) family, also known as TNFα converter (TACE), mediates ACE2 shedding on the membrane in response to RAS mediated signaling (Lambert et al, 2005), was expressed in AEPs (Supplementary Figure S1G).…”
Section: Aeps(supplementarymentioning
confidence: 99%